IMPLEMENTATION OF THE BILAL MAYIT ASSISTANCE PROGRAM POLICY IN THE SELAI DISTRICT OF LANGKAT DISTRICT (Pena Cendekia Insani, 2026)
Bilal corpses or socio-religious-based corpse management officers carry out community service duties, but often do not have a fixed wage system or formal social protection. The implementation of the Bilal Mayit assistance program policy is regulated in Langkat Regent Regulation Number 4 of 2022 concerning Procedures for Budgeting, Implementation and Administration of Reporting and Accountability as well as Monitoring and Evaluation of Grants and Social Assistance Sourced from the Regional Revenue and Expenditure Budget. This article will answer how the bilal mayit program policy is implemented in Finish District, Langkat Regency and what factors hinder implementation. This paper uses descriptive qualitative methods. Data was obtained through observation, interviews and literature study. The results of the research found that the sub-district government together with the village government had attempted to implement the program in accordance with applicable regulations. The communication aspect between program implementers has gone quite well through coordination between sub-district and village parties. Apart from that, the support from government officials and the community also helps the smooth implementation of the bilal deceased assistance program.